Nephropathy in the course of IgA vasculitis – case report - Dyga, Katarzyna; Jaszczura, Majka; Adamczyk, Piotr; Bjanid, Omar; Morawiec-Knysak, Aurelia; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2018)
IgA vasculitis (IgAV), formerly known as Henoch-Schönlein purpura (HSP), is the most common form of systemic vasculitis in children. Nephrological symptoms in the course of the disease are observed in 30–50% of children. The prognosis for maintaining normal kidney function is good in most patients; however, it depends on the primary clinical manifestation. Our aim was to present a case of a girl with nephropathy in the course of IgAV in the form of nephritic-nephrotic syndrome, who, despite early and intensive immunosuppressive treatment, revealed development of end-stage renal failure (ESRF) within two years. We also discuss the treatment of severe nephropathy in the course of IgAV, in accordance with current recommendations, which still remains a great challenge and does not guarantee slower progression of the disease.